Stratigraphic Model of East Biak Based on Magnetotelluric Data - Alviyanda Alviyanda; Gusti Muhammad Lucki Junursyah; Prihadi Sumintadireja (Institute for Research and Community Services (LPPM) ITB, 2020)
Biak Island is thought to have originated from the Australian Continental passive margin in the Mesozoic. This passive margin underwent tectonic collision to form the bedrock of Biak Island during the Paleogene. East Biak is covered by limestone, which is an obstacle to knowing the deeper stratigraphy. This study's aim was to identify the subsurface geology of the East Biak area based on rock resistivity values. Magnetotelluric (MT) surveying is a passive geophysical method that is able to interpret subsurface geology based on rock resistivity values at depths of up to 5 to 10 km. The MT measurements in East Biak used 25 measurement points. Cross-sectional variations in rock resistivity values generated from the MT measurements were used to identify rock types in the East Biak subsurface. Five rock units were identified. The East Biak stratigraphy model is dominated by carbonates, comprising two sequences, i.e. an Early Neogene sequence with a thickness of 1,000 to 3,000 m and a Late Neogene to Quaternary sequence with a thickness of 180 to 2,450 m. The unconformity between these two sequences is due to tectonic activity, which separated Supiori and Biak Island.